Philanthropy without borders: Calouste Gulbenkians founding vision for the Gulbenkian Foundation - Conlin,Jonathan (2010)
Established on his death in 1955, the Armenian oil magnate Calouste Sarkis Gulbenkians eponymous foundation enjoys a high profile in the cultural life of Lisbon and Portugal as a whole. Gulbenkians correspondence as well as that which passed among Cyril Radcliffe, José de Azeredo Perdigão, and others involved in helping plan and then establish the Calouste Gulbenkian Foundation indicates that the parameters of the latters activities were much fought over in its early years. The course set by the Foundation under Salazars dictatorship does not reflect the benefactors original intentions, which anticipated more recent models of charitable giving in their scope and dynamism.